Nutritional contents and antimicrobial activity of the culinary-medicinal mushroom Leccinum scabrum - M.L. Gargano; G. Balenzano; G. Venturella; M.M. Cavalluzzi; N.P. Rotondo; G. Lentini; F. Cirlincione; G. Mirabile; E. Zapora; M. Wołkowycki; L. Pecoraro; V. Ferraro (Mycology)
Leccinum scabrum (Bull.) Gray (Boletaceae) is an edible mycorrhizal species with potential application interest due to its food and medicinal properties. A field investigation carried out during summer in the Białowieża Primeval Forest, located along the border between Belarus and Poland allowed to collect samples for chemical composition analysis and antibacterial activity evaluation. Mushroom extracts were prepared with microwave-assisted as well as ultrasound-assisted extraction techniques (UAE and MAE). The analysis of a dry sample of L. scabrum showed a significant content of vitamins and minerals and also a remarkable content of carbohydrates, protein, dietary fibre, total sugars, total free amino acids, and polyunsaturated fatty acids. The antibacterial activity of L. scabrum aqueous extracts showed inhibitory activity against all tested bacteria. In general, MAE extract exhibits a higher inhibition activity against Listeria monocytogenes ATCC 19114. As regards the Minimum Inhibitory Concentration (MIC) values, the high antibacterial activity of MAE extract was detected for L. monocytogenes ATCC 19114 and Escherichia coli ATCC 25922. Regarding UAE, high antibacterial activity was detected for Salmonella enterica ATCC 13076 and L. monocytogenes ATCC 19114. Based on data hereby reported, L. scabrum is a culinary-medicinal mushroom with a promising potential use as a high-quality food and nutraceutical mycological resource.